No sex-based difference in cardiogenic shock: A post-hoc analysis of the DOREMI trial. Issue 4 (October 2022) - Prosperi-Porta, Graeme; Motazedian, Pouya; Di Santo, Pietro; Jung, Richard G.; Parlow, Simon; Abdel-Razek, Omar; Simard, Trevor; Hutson, Jordan; Malhotra, Nikita; Fu, Angel; Ramirez, F. Daniel; Froeschl, Michael; et al.
Abstract: Background: Cardiogenic shock (CS) is associated with significant morbidity and mortality; however, there are limited randomized data evaluating the association between sex and clinical outcomes in patients with CS. Patients with CS enrolled in the DObutamine compaREd with MIlrinone (DOREMI) trial were evaluated in this post-hoc analysis. Methods: The primary outcome was a composite of all-cause mortality, resuscitated cardiac arrest, cardiac transplant or mechanical circulatory support, non-fatal myocardial infarction, transient ischemic attack or stroke, or initiation of renal replacement therapy. Secondary outcomes included the individual components of the primary outcome. We analyzed the primary and secondary outcomes using unadjusted relative risks and performed adjusted analysis for the primary outcome and all-cause mortality using the covariates mean arterial pressure <70 mmHg at inotrope initiation, age, and acute myocardial infarction CS. Results: Among 192 participants in the DOREMI study, 70 patients (36 %) were female. The primary outcome occurred in 38 female patients (54 %) compared to 61 male patients (50 %) [adjusted relative risk (aRR) 1.23; 95 % CI 0.78–1.95, p = 0.97]. When stratified by inotrope, there was no difference in the primary outcome comparing females to males receiving dobutamine (RR 1.14; 95 % CI 0.79–1.65, p = 0.50) nor milrinone (RR 1.03; 95 % CI 0.68–1.57, p = 0.87). There was no difference in all-cause mortality comparing females to males (aRR 1.51; 95 % CI 0.78–2.94, p = 0.88). Additionally, there were no differences in any secondary outcomes between males and females ( p > 0.05 for all endpoints). Conclusion: In patients presenting with CS treated with milrinone or dobutamine, no differences in clinical outcomes were observed between males and females. Graphical abstract: No sex-based difference in cardiogenic shock: a post-hoc analysis of the DOREMI trial. Unlabelled Image Highlights: Adverse clinical outcomes in cardiogenic shock (CS) are not associated with sex. Sex does not influence outcomes in CS when treated with milrinone nor dobutamine. Women with CS have lower mean arterial pressure, heart rate, and creatinine.